Promoting High Quality Development of Coal Industry with Safety Intelligent Innovation and Green “Four Wheel Drive” - SUN Wei, LIN Qing, ZHAO Hongfei (Meikuang Anquan, 2020)
Under the background of China’s economy from high-speed development to high-quality development, the development of coal industry has entered a critical transition period. Safety, intelligence, innovation and green have become the “four elements” and boosters of high-quality development of coal industry. Based on the safety development, Wanbei Coal and Power Group Company actively responds to the intelligent development trend of coal industry, gives play to the lasting power of :“four-wheel drive” and promotes the transformation and high-quality development of the coal industry through continuous scientific and technological innovation and green development.